Investasi dan Faktor-Faktor Ekonomi yang Mempengaruhinya di Propinsi Papua Barat - Martha Agusthina Corry Kareth (EKO-REGIONAL, 2012)
ABSTRACT Aim of this research is to analysis of investment and economic macro variables in the West Papua Province. The dependent variable is Investment (Y), while the independent variables which are the target of observation is the Economic Growth variable (X1), the infrastucture (X2), labor variable (X3) dan inflation rate variable (X4). Data used in this study originated from the BPS, BI and the BKPMD of West Papua Province. The method used in this study is Granger Causality test. Results shows that economic growth variable, infrastructure variable and labor variable has a positive direction and significantly affecting investment variable at 5 percent level while the inflation rate has a negative direction and not significant at level 5 percent. Keywords: investment, economic growth, infrastructure, labor